Cyanobacteria and microalgae associated with mosses in wet meadows (High Arctic) - Polášková, Anna (Jihočeská univerzita, 2018)
Associations of nitrogen fixing cyanobacteria with mosses in wet meadow habitats of central Svalbard are of significant ecological importance as they represent a dominant nitrogen source. The first aim of this thesis was to find a suitable method to mechanically dislodge cyanobacteria from the moss stems, which would allow subsequent cyanobacterial identification and quantification. The second aim was to perform pilot Sanger sequencing which would allow to obtain another assessment of the cyanobacterial community for future studies of the wet meadow.
Cyanobacteria and microalgae associated with mosses in wet meadows (High Arctic)
Keywords: moss-associated cyanobacteria; dislodging methods; pilot Sanger sequencing; wet meadows; High Arctic; moss-associated cyanobacteria; dislodging methods; pilot Sanger sequencing; wet meadows; High Arctic